The usage of botulinum in the treatment of masticatory muscles hyperactivity - Martyna Drożak; Paulina Grabowy; Paulina Drożak (Kazimierz Wielki University, 2022)
Introduction and purpose: Masticatory muscles hyperactivity is currently a very common problem among adult population. The ignorance of the symptoms and the lack or unsuccessful treatment may lead to serious health complications, which lead to major focus on improvement of the standard therapy for bruxism. The aim of the study was to provide a broad review on the promising treatment of bruxism symptoms with botulinum neurotoxin injections. Material and method: The review was conducted based on an available literature on PubMed database, searching the following phrases: bruxism, botulinum neurotoxin. Results: As bruxism has a very complex etiology, the treatment can not be narrowed down to one therapy system. Despite the fact that botulinum neurotoxin injections can not solve the primary reason of bruxism occurrence, it has shown excellent results in treatment of symptoms, since the substance has an ability to induce muscle relaxation. Therefore, such pain relief substance has shown a much better performance and long lasting results in comparison to drug therapy or behavioral treatment. Conclusions: The research confirmed that the usage of botulinum in the treatment of masticatory muscles hyperactivity is safe, well-tolerated by the patients and shows satisfying results. Conducted studies have proven that the most effective way of bruxism treatment is a therapy, which tackles both complex etiology of the disorder and its symptoms.